In Vitro and In Vivo Effect of Xylopic Acid on Cytochrome P450 Enzymes - Mary A. Agbenyeku; Regina Appiah-Opong; Ernest Obese; Robert P. Biney; Emmanuel A. Adakudugu; Arnold D. Forkuo; Silas A. Osei; Mustapha K. Abeka; Elvis O. Ameyaw (Advances in Pharmacological and Pharmaceutical Sciences)
Introduction. Xylopic acid (XA), the major constituent of the fruit of Xylopia aethiopica, has shown several pharmacological properties. Traditionally, the plant is used to treat several diseases and is being used in the preparation of several local foods despite the lack of information about its safety, food-drug interaction, and other pharmacokinetic properties. This study, therefore, investigated the effect of XA on rat liver cytochrome P450 (CYP) enzymes in vivo and in vitro. Methods. Inhibition or induction of some isoforms of CYP450 enzymes: CYP 1A1/1A2, 1A2, 2B1/2B2, 3A4, 2D6, and 2C9 were investigated using microsomal fractions of the liver obtained from rats pretreated with a low dose of xylopic acid (LDT) 30 mg/kg, high dose of xylopic acid (HDT) 100 mg/kg, phenobarbitone (PC) 80 mg/kg, and ketoconazole (NC) 100 mg/kg, and a no-treatment group received distilled water, with (n = 5) animals in each group. The in vitro inhibition of CYP 3A4 was assessed by treating rat liver microsomes with XA. Results. Xylopic acid induced CYP 1A1/1A2, 1A2, 2D6, and 2C9, inhibited CYP 3A4, and had no effect on 2B1/2B2. Conclusion. The findings would help mitigate toxicity and therapeutic failure especially in cases of coadministration of medications with food containing XA, with metabolism altered by the latter.